Formation by yeast of 2-furanmethanethiol and ethyl 2-mercaptopropionate aroma compounds in Japanese soy sauce. Issue 1 (2nd January 2014) - Meng, Qi; Hatakeyama, Makoto; Sugawara, Etsuko
Abstract: Two aroma compounds of volatile thiols, 2-furanmethanethiol (2FM) and ethyl 2-mercaptopropionate (ET2MP), were formed in five types of Japanese soy sauce during fermentation by yeast. The concentrations of 2FM and ET2MP in the soy sauce samples increased during alcoholic fermentation. The concentrations of 2FM and ET2MP were higher in the soy sauce fermented by Zygosaccharomyces rouxii than in that fermented by Candida versatilis . The enantiomers of ET2MP were separated by gas chromatography in a capillary column. The average enantiomeric ratio of ET2MP in the soy sauce was approximately 1:1. 2FM was formed by yeast in a medium prepared from cysteine and furfural, and cysteine is considered the key precursor of 2FM by yeast in soy sauce. Graphical abstract: : Two important aroma compounds of volatile thiols, 2-furanmethanethiol etc., were formed in Japanese soy sauce during fermentation by yeast.